Testing the effect of belief adjustment model and overconfidence on investment decision making - Rofiyah, Farita Dewi; Almilia, Luciana Spica (The Indonesian Accounting Review, 2017)
This study aims to examine the effect of belief adjustment models, consisting of presenta-tion pattern (Step by Step and End of Sequence), information sequence, and information series, on investment decision making. In addition, this study also examines the effect of the level of overconfidence on investment decision making. The designs of experiment included in this study are presentation pattern 2 × 2 × 2 × 2 (Step by Step and End of Sequence), information sequences (good news followed by bad news and bad news fol-lowed by good news), information series (long series and short series), and the level of overconfidence. The research hypotheses are tested using Independent Sample t-test. The results of this study show that there is a recency effect on the presentation pattern of the Step by Step for long and short information series. This is also reflected in the End of Sequence which shows that there is no recency effect occurring in the long series, but there is recency effect occurring in the short series.